A Positive Role of Negative Mood on Creativity: The Opportunity in the Crisis of the COVID-19 Epidemic - Du, Ying; Yang, Yilong; Wang, Xuewei; Xie, Cong; Liu, Chunyu; Hu, Weiping; Li, Yadan (Frontiers in Psychology, 2021)
Abstract: The COVID-19 epidemic is associated with negative mood, which has the potential to be a powerful driver of creativity. However, the influence of negative mood on cognitive creativity and emotional creativity remains elusive. Previous research has indicated that self-focused attention is likely to be related to both negative mood and creativity. The current study introduced two variables of self-focused attention (i.e., rumination, reflection) to explore how negative mood might contribute to cognitive creativity and emotional creativity. Based on a sample of 352 participants, our study found that (1) negative mood during the outbreak of COVID-19 associated with cognitive creativity and emotional creativity. Meanwhile, there were significant serial mediation effects of rumination and reflection in the relationship between negative mood and creativity; (2) the psychological impact after exposure to the COVID-19 epidemic was positively correlated with emotional creativity but not with cognitive creativity. These results suggested that individuals, in real life and work, could achieve better creative performance through moderate self-focus. And individuals with different mood states can be conducted to enhance their creativity in times of crisis through intervention training to promote reflection.